SHELLAC RESIN EFFECT ON THE PROPERTIES OF ZEIN FILM - Šuput, Danijela; Popović, Senka; Hromiš, Nevena; Pantić, Jovana; Ločar, Biljana; Pezo, Lato (Journal on Processing and Energy in Agriculture, 2023)
In this work, zein-based films with the addition of shellac were synthesized and characterized. Shellac was added in two ways: (1) by lamination on the existing dry zein film (samples marked as L), (2) by adding shellac alcohol solution during the synthesis of zein film in a ratio of 50-50 by casting process (samples marked as M). Zein films without the addition of shellac were designated as control samples. Physico-chemical (thickness, moisture content and swelling), mechanical (tensile strength and elongation at break) and barrier characteristics (water vapor permeability) were examined for all sample groups. The resulting films are transparent, glossy, light yellow (control) to ocher (samples with added shellac), flexible, non-sticky. The results showed significantly higher values of elongation at break in samples to which shellac was added compared to the control sample. These values are higher for laminated samples. Also, significantly lower water vapor permeability values were found, 10.04 g/(m2·h) for L samples, 18.41 g/(m2·h) for M samples, compared to the control pure zein film (40.33 g/(m2·h)), which is also the biggest contribution of this work. Optimizing the production process, as well as the properties of the obtained biopolymer films, directly affects the expansion of their application.